Povos bárbaros ou fieis vassalos? luta, negociação e protagonismo indígena diante do devassamento do Sertão da Farinha Podre e áreas contíguas (1750 - 1850) - Oliveira, Ricardo Batista de (2016)
The present thesis analyses a new aspect of the indigenous people of Sertão da Farinha Podre, (current Triângulo Mineiro), adjacent areas of Goiás, São Paulo and current Mato Grosso do Sul. There is a reflection on cultural exchanges established by the Indians with people of other "qualities", with associations, periods of accommodation and permanence, as well as, breaks, political mobilization and in their most varied expressions of resistance, considering, however, the asymmetrical aspects of the relations established between Indians and non-Indians. Besides understanding under which circumstances the Indians aggravated their resistance through confrontation, we verified when several groups had framed alliances with non-Indians and the consequences of such alliances. Indigenous politics throughout Brazil was complex, and ambiguous taken in some regions, as noted in the capitania of Goiás. There were various manners of indigenous resistance, not only military confrontation, but mainly approaches, alliances and obtainance of some advantage on the pressures triggered on them from the mid-18th century. We understand that culture is not a monolithic block, being a in constant transformation. Thereby we embrace studies that value the idea of "cultural interaction" in opposition to the treatment of culture in a pure form and crystallized. In this study, we face the indigenous history beyond the fatality and destruction.